Congenital unilateral facial palsy revealing a facial nerve agenesis: a case report and review of the literature - Nordjoe, Yaotse Elikplim (BJR Case Rep, 2018)
Facial nerve aplasia is an extremely rare condition that is usually syndromic, namely, in Moebius syndrome. The occurrence of isolated agenesis of facial nerve is even rarer, with only few cases reported in the literature. We report a case of congenital facial paralysis due to facial nerve aplasia diagnosed on MRI, while no noticeable abnormality was detected on the temporal bone CT.